The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jerd.12304
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional stereophotogrammetric analysis of 50 smiles: A study of dento‐facial proportions

Abstract: If the distances from reference points of the face to teeth within a harmonious smile exhibited recurring esthetic proportions, knowledge of such ratios would provide an additional tool for the elaboration of esthetic treatment plans. In addition, this knowledge could provide guidance when planning tooth positions and dental proportions by encouraging consideration of the global nature of the oro-facial sphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…Ceinos et al obtained the ratio of 1.60260.136 "right labial commissure-left labial commissure/distal edge of the right canine-distal edge of the left canine" in their study of dentofacial ratio analysis. 18 In this study, this ratio was found to be 1.66 in males and 1.59 in females, respectively. This ratio can be especially important because the teeth and lips are important components of a smile.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Ceinos et al obtained the ratio of 1.60260.136 "right labial commissure-left labial commissure/distal edge of the right canine-distal edge of the left canine" in their study of dentofacial ratio analysis. 18 In this study, this ratio was found to be 1.66 in males and 1.59 in females, respectively. This ratio can be especially important because the teeth and lips are important components of a smile.…”
Section: Discussionmentioning
confidence: 46%
“…In a study by Ceinos et al, this ratio was found to be 1.67060.355. 18 Hasanreisoglu et al obtained an average A/C ratio of 1.618 for both genders in groups representing the Turkish population. 8 Nikgoo et al reported that the golden ratio can be used to restore the maxillary central and lateral teeth anesthetically.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Orientierungshilfen bei der kieferorthopädischen Behandlung dienen, um ein funktionelles / dentofaziales Gleichgewicht zu erreichen (Ceinos et al 2017).…”
Section: Zukünftig Könnten Erkenntnisse üBer Diese Zusammenhänge Alsunclassified
“…Auch zur Veränderung von Weichteilen durch Zahnbewegungen wurden Untersuchungen durchgeführt (Sawyer et al 2009;Kim et al 2014;Galantucci et al 2016;Ceinos et al 2017;Celebi et al 2017;Jang et al 2017;Masoud et al 2017). Die Reproduzierbarkeit des Setzens von definierten anatomischen Punkten, sogenannte landmarks, ist für nachfolgende Auswertungen wichtig.…”
Section: Index Of Treatment Needunclassified